BODIPY-based conjugated microporous polymers as reusable heterogeneous photosensitisers in a photochemical flow reactor. Issue 43 (17th October 2016) - Tobin, J. M.; Liu, J.; Hayes, H.; Demleitner, M.; Ellis, D.; Arrighi, V.; Xu, Z.; Vilela, F.
Abstract : Production of singlet oxygen at 530 nm in a flow reactor using novel BODIPY-based polymers as heterogeneous photosensitisers. Abstract : BODIPY-based conjugated microporous polymers (BDP_CMP and PHTT_BDP) have been synthesised via two distinct methods of assembly: high-yielding Suzuki–Miyaura cross-coupling of BODIPY-containing building blocks, and post-synthetic conversion of an aldehyde-equipped CMP host that was synthesised in the absence of metal-based catalysts. Both approaches yielded BODIPY-based materials featuring a high BET surface area (484–769 m 2 g −1 ) and a bathochromic shift in the maximum light absorbance (520–550 nm). Singlet oxygen production employing the BODIPY-based materials at 530 nm was carried out heterogeneously in a commercial photochemical flow reactor.